2019
DOI: 10.1111/nep.13582
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of biopsy‐proven renal disease in northern India: A single‐centre study

Abstract: Aim Pattern of kidney diseases varies across geographies due to multiple factors. There is a paucity of information from South Asia due to the absence of nationwide/regional biopsy registries. This study aimed to delineate the spectrum of renal parenchymal diseases in our region. Methods Records of kidney biopsies done in our nephrology department between 2006 and 2016 were analysed. Clinico‐pathological correlation was done from the available records. Results Of the 3275 biopsy evaluated, 61.9% were males, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
(167 reference statements)
6
14
0
Order By: Relevance
“…In our study, NS was the most common clinical indication for renal biopsy, followed by nephritic syndrome (Table 2). These results are consistent with most previous reports 12,28,35,36 , including those from several centers in China 7,8,19 , but not those from Japan (nephritic syndrome followed by NS) 37 , South Korea (AUA, followed by NS) 25 , and one report with a smaller number of cases from Central China (proteinuria and hematuria, followed by NS) 22 . Variation in renal biopsy policies and in diagnostic criteria of histopathological diagnoses may be the reasons of the above-mentioned discrepancies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, NS was the most common clinical indication for renal biopsy, followed by nephritic syndrome (Table 2). These results are consistent with most previous reports 12,28,35,36 , including those from several centers in China 7,8,19 , but not those from Japan (nephritic syndrome followed by NS) 37 , South Korea (AUA, followed by NS) 25 , and one report with a smaller number of cases from Central China (proteinuria and hematuria, followed by NS) 22 . Variation in renal biopsy policies and in diagnostic criteria of histopathological diagnoses may be the reasons of the above-mentioned discrepancies.…”
Section: Discussionsupporting
confidence: 92%
“…3). In adults, LN remains the most common SGN, although prevalence has significantly decreased over time, which is compatible with most studies 7,15,22,23,25,28 , but differs from the report from Northeast China which showed HSPN as the most common SGN followed by LN 8 . Additionally, a significant decrease in the prevalence of HBV-GN (MN pattern: 881 cases, MPGN pattern: 69 cases) was also observed from period 1 to period 2 (5.24% vs 1.12%, P = 0.0487)( Table 3 and Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to our results, a study on glomerular disease showed that 492 (54.85%) out of 897 patients with glomerular disease in Xinjiang were females [ 15 ]. The high-risk group of NS in the two regions was 22-47 years old, indicating that NS is most common in young people, which is consistent with the results of a study from India [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Mass spectrometry has significantly improved the ability to determine the type of amyloidosis and is a useful adjunct to renal biopsy. [ 80 ] Renal involvement is common with varying rates of prevelance in India from 3.7%[ 81 ] to 8%. Histologically, renal amyloid depositis are weak positive for periodic acid Schiff staining, distinguishing it from the collagenous composition of the basement membrane.…”
Section: Introductionmentioning
confidence: 99%